Pengembangan Bahan Ajar Kimia Materi Hidrolisis Garam dengan Pendekatan Scientific Inquiry Berbasis Problem Based Learning - wiji chusnah; Suhadi Ibnu; Sutrisno Sutrisno (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This development research aims to produce chemical teaching material products with a problem-based scientific inquiry approach based on the 4-D (four-D) model of Thiagarajan, Semmel and Semmel with the stages of define, design, develop, disseminate through a cross-sectional survey. The method used in the survey at the define stage is through literature review of chemistry textbooks. The results of the development of chemistry teaching materials salt hydrolysis material are empirically validated by content experts and chemistry learning material experts are considered valid with an average score of 3.67 and suitable for use as teaching materials.Abstrak: Penelitian pengembangan ini bertujuan untuk menghasilkan produk bahan ajar kimia dengan pendekatan scientific inquiry berbasis problem based learning model 4-D (four-D) Thiagarajan, Semmel dan Semmel dengan tahapan define, design, develop, disseminate melalui survey cross secsional. Metode yang digunakan dalam survei pada tahap define melalui kajian literatur buku teks pelajaran kimia. Hasil pengembangan bahan ajar kimia materi hidrolisis garam tervalidasi secara empirik oleh ahli isi dan ahli materi pembelajaran kimia dinilai valid dengan skor rata-rata 3,67 dan layak digunakan sebagai bahan ajar.